(untitled) (Linguostylistic Studies, 2016)
The article considers the peculiarities of Polissyan dialects on morphological level, including specificity of nouns, adjectives and verbs form-building, differences in pronoun structure and conjugation, in numerals and adverbs processing. The author places impotance on the morphological level, since it is fully and systematically reflected in the novel «Leaves of the Land» by Ukrainian writer Volodymyr Drozd. Polissyan word forms used by the writer are systematized and commented in terms of their origin. The emphasis is laid on the specificity of use of the Polissyan patois elements by the author and the function of the dialectal words in the artistic language. V. Drozd uses elements of dialects only in very lengthy stories and memoirs of the characters (traditional dialogues in the novel, in fact, are absent), while the author’s speech at a level of inflection is oriented to literary standard. The article concludes that this phenomenon is justified in view of the desire of the author most accurately and fairly reflect the local flavor of the language, and individualize characters’ speech and thus provide expressiveness. Key words: Polissyan dialect, inflections, archaism, innovation, grammatical analogy. References